Countermeasures to promote the systematic construction of the military IoT - Shibin LAN; Wenxiang XIA (物联网学报)
The military Internet of things (MIoT) is an important part of the military network information system.Based on this,the significance of MIoT systematic construction were described firstly.Then the main contents of construction of MIoT was provided,such as sensing network system,public architecture service system,standard specification system,security system and demonstration project.Finally,the countermeasures of promoting the systematic construction of MIoT were discussed.